Innovation Diligence – A Case Study of a Methodology for Technology Evaluation in the Technology Transfer Offices from Brazil - Ribeiro, Artur Tavares Vilas Boas (2019)
The Technology Innovation Agencies in Brazil are a recent phenomenon still in the maturing process. Inspired by the Technology Transfer/Licensing Offices, they have the challenge to encourage the diffusion of knowledge from universities and research centers in order to promote innovation and economic development. For many reasons, the context of the Brazilian Agencies is characterized by the absence of support and the scarcity of human resources, with small teams and a small institutional structure to fulfill their mission. Therefore, the process of technology transfer and fostering innovation becomes harder than usual, and no much expertise about how can these Agencies tackle the challenges for innovation. The article presents a methodology to support the process of technology transfer in the Brazilian context. The research is based on a case study and the data was collected through interviews and internal documents of an organization that has been working in partnership with these agencies in several regions of Brazil. The results stand out for the novelty of proposing a formalized process to evaluate technologies for transference in contexts of low resources. In addition, the article presents good practices and specific challenges in the final discussions. The main goal is to support the agencies and to improve the study of mechanisms for the technology transfer process.